Seneca’s Phoenissae: Anger and the myth of oedipus - Sanches, Cíntia Martins [UNESP] (My University, 2018)
The myth of Oedipus for Seneca, as presented in his tragedy Phoenissae, concerns extreme passions and their consequences. The two excerpts making up the unfinished Phoenissae base on two distinct opposites - reason and emotion. In both parts of the text, the female is associated with reason and balance, and the male with extreme emotions and furore. Antigone, in the first part of Phoenissae, tries to convince Oedipus not to commit suicide using arguments about his innocence, the possibility of preventing the war to be declared by Eteocles and Polynices on Thebes, and suchlike. In the second part, it is Jocasta who holds the reason before the thoughtless fight for the throne between her children and tries to convince them to stop fighting. This subject matter is directly related to the philosophy of Seneca, since there is a close proximity between the behaviour of the individual possessed by anger - present in the philosophical works of Seneca himself and other Stoics- and the anger of tragic characters, e.g. Oedipus, Eteocles and Polynices appearing in the aforementioned drama. This reflection shows us how the myth of Oedipus was related to the Roman culture (by means of Stoicism) at the time that the work was written. The present study investigates how the theme of “reason versus emotion” was introduced to Seneca’s tragedy and what was its relation to the Stoic philosophy. The word manus, which appears frequently in the text, has several meanings relevant to this theme, mainly because it refers alternatively to violence and restraint.
Keywords: Anger; Manus; Oedipus’ myth; Phoenissae; Seneca